Exploring the impact of xenobiotic drugs on forensic entomology for accurate post-mortem interval estimation - Jain, Sapna; Parrott, Jonathan J.; Javan, Gulnaz T. (Frontiers in Insect Science, 2025)
Forensic entomotoxicology is an emerging field within forensic entomology that investigates the effects of chemicals, drugs, and toxins on insect development and their implications for postmortem interval (PMI) estimation. This systematic overview delves into the influence of drugs such as Morphine, heroin, Opiates, and cocaine on the variables affecting the use of forensically significant insects as evidence tools. Notably, it has been observed that the presence of drugs does not appear to alter the progression of the lifecycle from the first instar to the emergence of flies, indicating that PMI estimations based on fly emergence remain unaffected by drugs. However, larvae treated with drugs frequently show delayed pupation, suggesting the need for further research into the impact of different compounds on various insect species over more extended observation periods. Additionally, conflicting results have been noted regarding how toxins can influence the developmental process in larvae, underscoring the necessity to assess the effect of different classes of compounds on other insect species. The study also recommends exploring factors such as the samples’ collection site and the drugs’ pathological implications to inspire future research. Furthermore, the paper underscores the potential for varying drug effects across insect species, emphasizing the complexity of interpreting drug impacts on PMI estimations. This systematic review was conducted by the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines.